IMPLEMENTASI PENGONTROLAN AIR CONDITIONER (AC) BERBASIS PENGOLAHAN CITRA UNTUK EFISIENSI ENERGI DI STUDIO MUSIK ZULJILAN RECORD - Febriansyah, Aan; Irwan, Irwan; Permatasari R, Herda Fitri; Nur Mushthafa, Ery (Jurnal Pengabdian Masyarakat Polmanbabel, 2025)
Efficient electricity use in office spaces is a crucial effort to support sustainability and reduce operational costs. This devotion aims to implement an air conditioner (AC) control system based on image processing in the Zulzilan Record music studio to enhance energy efficiency. The system utilizes camera technology to detect and count the number of people in the room in real-time. This information is used to automatically adjust the AC's temperature and power, aligning cooling needs with the desired temperature range. The implementation involves installing hardware and software for the image processing system and providing training for Zuljilan Record's operational staff on the proper use of the developed tool. Test results show that the system can detect the number of people with an accuracy of up to 92% and maintain room temperatures within the range of 20-25°C. Additionally, the system improves user comfort and contributes to operational cost savings. The positive impacts of this initiative include reduced operational costs, improved energy efficiency, and the adoption of environmentally friendly technology. This implementation is expected to serve as a model for other institutions to apply similar innovations, supporting energy efficiency and environmental sustainability.